Książka w życiu współczesnego dziecka. Animacja czytelnictwa dziecięcego i formy działalności Biblioteki Brytyjskiej na rzecz najmłodszych odbiorców literatury - Mikołajuk, Lidia (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The British Council is the United Kingdom's international organisation for educational opportunities and cultural relations. Its purpose is to build mutually beneficial relationships between people in the UK and other countries and to increase appreciation of the UK's creative ideas and achievements. It is present in over 100 countries worldwide. The British Council in Poland started in 1938, when its Polish office was established in Warsaw. The organization provides access to extensive British literature and cultural resources through a countrywide network of British Libraries. The paper presets the British Library in Łódź and its projects for young readers.